Chemoprevention of lung tumorigenesis by intranasally administered diindolylmethane in A/J mice - Qian, Xuemin (Oxford University Press, 2013)
The main reasons for the failure of most chemopreventive agents during clinical trials are poor in vivo bioavailability and dose-limiting side effects. One potential approach to surmount these problems in lung cancer chemoprevention trials could be direct delivery of agents into the pulmonary tissue. In this study, we assessed the efficacy of intranasally delivered bio-response diindolylmethane (BRD) against 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)-induced lung tumorigenesis in mice. Mice treated with NNK (two doses of 50mg/kg at an interval of a week, intraperitoneal) developed 16.3±2.9 lung tumors per mouse. Post-carcinogen administration of BRD, via intranasal instillation, for 24 weeks, twice a week, at a dose of 2mg per mouse (0.6mg pure diindolylmethane per mouse) reduced the lung tumor multiplicity to 4.6±2.2 tumors per mouse (72% reduction). Likewise, large tumors (>1mm) were almost completely abolished and multiplicities of tumors with a size of 0.5–1mm were reduced by 74%. Tumor volume was also reduced by 82%. Further studies using an in vitro model of lung tumorigenesis showed that BRD exhibited pronounced antiproliferative and apoptotic effects in premalignant and malignant bronchial cells but only minimal effects in parental immortalized cells through, at least in part, suppression of the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway. These results showed the potent lung tumor inhibitory activities of low doses of BRD given via intranasal instillation and, therefore, intranasal delivery of BRD holds a great promise for lung cancer chemoprevention in subjects at high risk to develop lung cancer.